Multy Variable Grey Method For Multy Point Deformation Analysis - Taşçi, Levent; Köse, Erkan (Fırat University, 2018)
Grey theory is one of the methods used to study uncertainty. The uncertain systems characterized by small sample and poor information are the study object of grey system theory. Multivariable grey prediction models are part of grey forecasting system. They are presented if there are mutual relations among the factors in the system. They believe that all the influencing factors are not independent of each other and should be regarded as a whole. In multivariable grey forecasting models, the future value of a variable is tried to be forecasted considering the other influential factors in the system. In this study, deformation consisting on the crest of a Dam is aimed to determine by using multivariable grey prediction models.
Keywords: Engineering; Mühendislik